Acoustic microphone array applications - Ang, Qian Shan (Nanyang Technological University, 2020)
In this report, a real time Blind Source Separation system will be created, whereby a microphone array is able to record and send recorded audio data into a central system via a network connection. Once the data is received, source separation is applied to achieve a multi-speaker speech recognition system. This will be done in real-time – small blocks of audio data will be sent as soon as it is recorded and the source will be separated in real time. A robust system will be created by ensuring data received is always complete and in the correct order. Performance will be optimised over a long period of time by compressing audio data when transmitting audio data. Finally, output of the system will be displayed.